Environmental risk perception of prospective biology teachers in Indonesia in the pandemic era - Rahardjanto, Abdulkadir; Husamah, Husamah; Sabilah, Fardini (Intelektual Pustaka Media Utama, 2024)
Environmental risk perception has a long-time travel in the public participation in environmental fields. This perception involves individually socially constructed physical and mental experiences that involve many factors just for knowledge, attitudes, and the culture that develops in society. An individual's understanding of environmental risk provides an overview of an individual's preparedness for appropriate environmental risk strategies and measures. This cross-sectional survey study aims to collect data on the environmental risk perception of Indonesian students. The survey data instrument used in this study is the environmental risk perception scale (ERPS) questionnaire, transformed into Google Forms in the Indonesian language. The target respondents were 1,267 students from 1,300 undergraduate population size of educational study programs in the field of biology who came from various institutions in Indonesia. Sexual category, grade point average (GPA), and university status to explore the perception of the active student environment of prospective biology teachers with various parameters. The results showed several interesting findings: the female sex is more sensitive to environmental risks, academic abilities play a more logical role in environmental risk analysis, and respondents who have taken environmental courses have a higher sensitivity to environmental risk.